Policy venue preference and relative trust in government in federal systems. Issue 2 (19th May 2020) - Leland, Suzanne; Chattopadhyay, Jacqueline; Maestas, Cherie; Piatak, Jaclyn
Abstract: This article defines a concept of relative trust—the gap between trust in different levels of government in a federalist system—and examines whether it influences public attitudes about which level of government holds authority in specific policy domains. While scholars have explored how trust in government affects political systems from a national perspective, little is known about how trust influences multitiered government systems in which public trust levels differ for national versus subnational governments. This article finds that greater relative trust in the state versus national level of government is associated with support for devolution in several policy areas where governing authority is shared: unemployment, health care, environmental policy, and food safety regulation. The implication is that relative trust shapes public preferences about policy centralization or decentralization and provides an individual‐level mechanism through which windows of opportunity open for changes in the allocation of policy authority.